The Effectiveness of Cooperative Learning Method (Student Team Achievement Divisions) in Christian Education - Sandy Ariawan (Universitas Muhammadiyah Mataram, 2018)
This study aimed to evaluate the use of cooperative learning method (Student Team Achievement Division) in character subject in Christian Education among State Vocational High School 8 Malang. A total of 26 students were involved in the study, separated in two classes. The first class was treated with Cooperative Learning Method and the other class as a control class. Student achievement was measured based on the pre-test and post-test. The result obtained from this study, using quasi-experimental design with paired sample T-test, sig. (0,002) < 0,05, indicated that the Cooperative Learning Method is effective in Christian education. From the finding of this study, it is recommended cooperative learning method as one of the appropriate method and practices in character building for Christian Education.